Sabang Agrotourism Area based on Essential Plants: Strategic Efforts in Improving Community Welfare - Suryani Sentosa, Dewi; Muhammad, Syaifullah; Muhibbuddin; Izziah; Amiren, Muslim; Zulfahrizal; Gusti Vonna, Adinda; Maulana, Muhammad Rizki; Yusuf, Rauzah; Keumalasari, Sofia; Marthunis (PT Inovasi Pratama Internasional, 2024)
The article explores the development of the Sabang Agrotourism Area, strategically focused on essential plants such as patchouli, cloves, and nutmeg, to enhance community welfare. Sabang City, situated in the westernmost region of Indonesia, is part of the National Tourism Strategic Area with abundant natural resources. The agricultural sector, covering 19.23% of the total area, has not fully tapped into the potential of agrotourism. The absence of agrotourism in Sabang City prompted a collaborative effort between Syiah Kuala University, Atsiri Research Center, and the Sabang Free Trade Zone and Free Port Concession Agency (BPKS). The community service approach utilized community-based learning and the Quadruple Helix model, involving academics, government, business, and the community. Through Focus Group Discussions (FGD), the team addressed short-term goals by discussing agrotourism potential and long-term goals of community empowerment. The findings reveal the extensive essential crop plantations in Sabang City, particularly patchouli, and cloves. Sabang's patchouli exhibits superior quality, with the highest yield value, making it an excellent candidate for export. Cloves, besides their economic value, serve as effective antioxidants and eco-friendly pesticides. The proposed Sabang Agrotourism Area includes five zones: Reception, Agro-tourism, Thematic Park, Family Garden, and Accommodation. Each zone caters to different activities, ensuring a holistic agrotourism experience. This community service contributes valuable insights and potential breakthroughs to policymakers, agrotourism developers, farmer groups, academics, and the broader community. The comprehensive analysis of Sabang's essential natural resources underscores the region's potential as a leading agrotourism destination. The proposed Agrotourism Area serves as a strategic step towards sustainable development, augmenting community income and well-being.